Surface Free Energy Estimation: A New Methodology for Solid Surfaces - (:unkn) unknown (WILEY, 2020)
An interpretation of solid surfaces is generated based on physical considerations and the laws of thermodynamics. Like the widely used Owens-Wendt (OW) method, the proposed method uses liquids for characterization. Each liquid provides an absolute lower bound on the surface energy with some uncertainty from measurement variations. If multiple liquids are employed, the largest lower bound is taken as the most accurate, with uncertainty due to measurement errors. The more liquids used, the more accurate is the greatest lower bound. This method links generalizations of the Good-Girifalco equation with a general thermodynamic inequality relating the three-interfacial tensions in a three-phase equilibrium system. The method always satisfies this inequality with better than a 65% certainty. However, the OW seldom, if ever, conforms to this inequality and even then, the degree of satisfaction is insignificant. A reconciliation of the two methods is proposed based on rescaling the OW surface energies to conform to the inequality. This enables interpretations of dispersion and polar components of the surface energy, which are thermodynamically self-consistent. The proposed method is also capable of dealing with material exchange between liquid and solid phases, when the surface tension and contact angle of the saturated liquids can be measured.
Keywords: contact angle; Good-Girifalco; Owens-Wendt; sessile drop; surface free energy; INTERFACIAL-TENSIONS; CONTACT ANGLES; SYSTEMS; COMPONENTS; POLYMERS; LIQUIDS; HEPTANE; FORCES